Synthesis and characterization of hierarchical multilayered flower-like assemblies of Ag doped Bi2WO6and their photocatalytic activities - Phattharanit Dumrongrojthanath (2018)
In this research, 0-3 mol% Ag doped Bi2WO6hierarchical multilayered flower-like assemblies were successfully synthesized by a simple hydrothermal method at 180 C for 24 h. The XRD, FE-SEM, FTIR and Raman analyses revealed the presence of flower-like Russellite Bi2WO6structures which were constructed from a large number of orderly arranged 2D layers of interconnected nanoplates. Their photocatalytic activities were evaluated by photodegradation of rhodamine B (RhB) under Xe visible light irradiation (λ > 420 nm). The 3 mol% Ag doped Bi2WO6showed the highest photocatalytic activities of 98.20% within 180 min. © 2013 Elsevier Ltd. All rights reserved.